Seasonal Variations in Wave Energy and the Changing Beach Characteristics: A Case Study of Beaches of Karachi - Syed Shahid Ali ,; Sheeba Afsar, (Journal of Basic & Applied Sciences, 2013)
The study of beach characteristics is generally described in terms of the relationship of wind velocity, wave energy, beach profile and grain size variation of the beach sediments. Most of the coastal research is concerned with investigating the behavior of water and sediments along the shoreline; these being the processes responsible for the formation of coastal land forms. The amount of erosion and depositional activities along a shoreline depends on the quantity of energy in the waves which are also responsible for bringing changes in the beach profile and hence beaches are classified on the bases of the impacts of these processes which are presented here in this paper.